1988
DOI: 10.1007/bf00609246
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enoxacin, ofloxacin and norfloxacin on theophylline disposition in humans

Abstract: The effect of three new fluoroquinolones on theophylline kinetics and the urinary excretion of metabolites was studied in 5 healthy subjects (3 male, 2 female). All subjects received serial, single i.v. infusions of theophylline (aminophylline, 250 mg) over 60 min after 200 mg doses of a quinolone (enoxacin, ofloxacin, norfloxacin) every 8 h for 3 consecutive days, the quinolone being administered up to the day following theophylline administration. Pretreatment with ofloxacin and norfloxacin did not influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…After treatment with enoxacin, the formation clearances of 3-MX, 1-MU, and 1,3-DMU, calculated from their urinary recoveries, showed significant decreases of 69 %, 59 %, and 38 %, respectively (Table 1). This finding agrees well with that reported by Sano et al [13]; enoxacin lowered the CLT of theophylline by inhibiting formation of the three metabolites, especially 3-MX and 1-MU. In contrast, after treatment with fluconazole, the extent of the reduction in the three formation clearances was only 15 %-18 %.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…After treatment with enoxacin, the formation clearances of 3-MX, 1-MU, and 1,3-DMU, calculated from their urinary recoveries, showed significant decreases of 69 %, 59 %, and 38 %, respectively (Table 1). This finding agrees well with that reported by Sano et al [13]; enoxacin lowered the CLT of theophylline by inhibiting formation of the three metabolites, especially 3-MX and 1-MU. In contrast, after treatment with fluconazole, the extent of the reduction in the three formation clearances was only 15 %-18 %.…”
Section: Discussionsupporting
confidence: 83%
“…Enoxacin, a quinolone antibacterial, potently inhibits the oxidative metabolism of theophylline [12,13]. Therefore, comparing test drugs and enoxacin should be a reasonable method of elucidating their potency in inhibiting cytochrome P-4501A-mediated theophylline metabolism in humans.…”
mentioning
confidence: 99%
“…By comparing the inhibitions between the quinolones in the in vitro human liver microsomal system, we found that the extent of inhibition can be graded as enoxacin > ciprofloxacin > norfloxacin. Sano et al (18) found that the mean cumulative urine recoveries of 3-MX, 1-MU, and 1,3-DMU in humans were decreased from that of control by 64, 63, and 28%, respectively, after administration of enoxacin. These results correlate well with those from our human liver microsomal system (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Theophylline and its metabolites in urine collected over a dosing interval were also measured on 5 June (no ipriflavone) and 6 August (during ipriflavone) by HPLC [3]. The recovery ratio of 3-methylxanthine was decreased from 17.9 to 11.5 % and of 1-methyluric acid from 29.1 to 25.5 %.…”
mentioning
confidence: 99%